2014
DOI: 10.1007/s11746-014-2530-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trans Fatty Acid Level in French Fries from Various Fast Food Outlets in Karachi, Pakistan

Abstract: The purpose of this study is to determine the trans fat level in French fries sold in different fast food outlets in Karachi. In the present study, attenuated total reflectance‐Fourier transform infrared (ATR‐FTIR) spectroscopy was used for the quantification of trans fatty acid (TFA). A number of studies have been reported on trans fat in different regions of the world, but no categorical study has yet discussed the trans fat in fast food products in Karachi. Amongst the samples examined, the total trans fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For some time now, frying methods and oils used have been progressively altered to minimize TFA presence in French fries. As is evident in Table 1 , better frying practices led to decreased TFA content from values around 30% in 1998 [ 64 ], and even up to 42% in 2006 [ 65 ], to values lower than 2% in more recent studies [ 17 , 19 , 69 ].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For some time now, frying methods and oils used have been progressively altered to minimize TFA presence in French fries. As is evident in Table 1 , better frying practices led to decreased TFA content from values around 30% in 1998 [ 64 ], and even up to 42% in 2006 [ 65 ], to values lower than 2% in more recent studies [ 17 , 19 , 69 ].…”
Section: Resultsmentioning
confidence: 98%
“…In the past few years many efforts have been made to reduce the presence and dietary intake of TFA in foods traditionally rich in TFA such as bakery products, snacks, margarines, fats, and fast foods with mixed success. This is the subject of elegant works carried out in Portugal [ 16 ], Pakistan [ 17 ], Brazil [ 18 ], UK [ 19 ], Austria [ 20 ], Costa Rica [ 21 ], Estonia [ 22 ], New Zealand [ 23 ], Switzerland [ 24 ], Serbia [ 25 ], or Lebanon [ 26 ]. Our research group conducted a study of bakery products and also in snacks commercialized in Spain and also found very low TFA in these products [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was significant variation observed in the fatty acid profile of all analyzed chips samples; however, high contents of palmitic acid and TFA were evident 23 . Karim et al 24 investigated TFA levels in French fries sold at different fast food outlets of Karachi. Among the samples analyzed, the TFA content for four outlets was in the range of 10‐24% of total fat.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, of the seven EMR countries listed above, Pakistan had the highest TFA content in food items such as French fries (range: 0.11-24.00% of TF) [17] and cereal based foods (range: 2.5-16.3% of TF) [19]. This is also true for TFA content in Iranian food products such as fast food (range: 23.6-30.7% of TF) [20], milk (range: 9.2-14.1% of TF), as well as junk foods and bakery items (range: 4.5-36.1% of TF) [21].…”
mentioning
confidence: 96%
“…SFA contribution to total fat in snack items differed per country. For example, SFA contribution to total fat in plain biscuits was 50.1% in Lebanon [31], 37.9-46.9% in Pakistan [30], and 33.6% in Iran [20).…”
mentioning
confidence: 99%